IDENTIFICATION OF PARTNERSHIP PATTERNS AND RICE DISTRIBUTION CHANNELS AS THE MAIN COMMODITY IN SIDENRENG RAPPANG DISTRICT - Aksal Mursalat; Ayu Wulandary; Fitriani R (Socio-Economics/Agribusiness Department, 2020)
Sidenreng Rappang Regency is one of the rice providers in South Sulawesi Province in supporting food self-sufficiency in Indonesia. However, there are several problems faced by farmers in Sidenreng Rappang Regency, namely farmers have not been able to optimize their production results due to limited information in determining selling prices, while through a partnership pattern it makes it easier for farmers to obtain information about marketing and other problems, namely the length of distribution channels experienced by farmers. causing the selling price of rice to be classified as very low. The purpose of this research is to identify or study the partnership patterns and distribution channels that have been carried out by rice farmers in Sidenreng Rappang Regency. This research was conducted in Sidenreng Rappang Regency which took place in May-August 2020. The method used was observation and interviews involving 10 rice farmer respondents, then the data were analyzed to determine the implementation of the partnership pattern in the form of a descriptive method and to detect the distribution pattern of rice commodities. Based on the results of the research, the partnership pattern in the rice distribution channel in Sidenreng Rappang Regency is included in the category of general trading patterns, namely by marketing unhulled grain products to rice milling companies through intermediary traders. The implementation of the rice distribution channel system begins with farmers - collectors - rice milling companies, then distributed to two business actors, namely large companies and retailers to the final level to consumers.